2016
DOI: 10.1017/s0267190515000069
|View full text |Cite
|
Sign up to set email alerts
|

Task-Based Versus Task-Supported Language Instruction: An Experimental Study

Abstract: This study investigated the effectiveness of task-based and task-supported instruction in the acquisition of the English passive construction—a structure about which learners had limited prior knowledge. A total of 150 Chinese middle school English as a foreign language (EFL) learners were randomly assigned to five groups—one control group who only took the pretest and posttests and four experimental groups who attended a 2-hour treatment session where they performed two dictogloss tasks in groups, each includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 40 publications
7
78
2
1
Order By: Relevance
“…The control can then be gradually decreased, after which learners engage in meaning-focused activities. This approach is compatible with the presentation-practice-production model (Sato, 2010) and task-supported language instruction (Li, Ellis, & Zhu, 2016). On the other hand, a "strong" view on task-based language teaching (Long, 2015) proposes that tasks should not focus on certain linguistic forms, and explicit instruction should not be prepared by teachers, which may seem incongruent with the idea of systematic and deliberate practice.…”
mentioning
confidence: 89%
“…The control can then be gradually decreased, after which learners engage in meaning-focused activities. This approach is compatible with the presentation-practice-production model (Sato, 2010) and task-supported language instruction (Li, Ellis, & Zhu, 2016). On the other hand, a "strong" view on task-based language teaching (Long, 2015) proposes that tasks should not focus on certain linguistic forms, and explicit instruction should not be prepared by teachers, which may seem incongruent with the idea of systematic and deliberate practice.…”
mentioning
confidence: 89%
“…Task‐supported research involving dynamic assessment might revitalize process–product studies. One recent CIT study that compared task‐supported and task‐based instruction (Li, Ellis, & Zhu, ) showed significant effects for explicit instruction in learners with some prior knowledge of the tested language features, but the authors note their study focused on the product, not the process. It would be interesting to know how a study that focused on processes and included CBI and DA would compare to traditional explicit instruction.…”
Section: Dynamic Assessmentmentioning
confidence: 99%
“…Research in this area typically are limited to two categories, namely (a) the impact of using specific technique or tool on learning (e.g. Campo, 2016;Li, et al, 2016) and (b) various tasks, teaching techniques, or media uses learning a particular task (e.g. Moore & Lorenzo, 2015;Lee, 2016;Ahmed, 2017); nevertheless, limited research is found in exploring students' experience in task-based learning activities.…”
Section: Introductionmentioning
confidence: 99%